State of solid waste disposal and suggested fixes for Iwo and Ibadan Metropolis, Nigeria - Jazat, J. P.; Akande, J. A.; Ogunbode, T. O. (Frontiers in Sustainability, 2023)
Factors governing stakeholders' choice of gathering and disposing of solid wastes in some southwestern states of Nigeria were appraised using Iwo and Ibadan as case studies. The objectives were to determine associated challenges and recommend possible improvements. The study administered 1,400 structured questionnaires, out of which 873 (62.3%) were respondents. The data obtained were analyzed using descriptive and inferential statistics. The result showed an upward trend in solid waste disposal in the two communities, according to stakeholders' income and household size. Solid wastes generally encountered in the study areas include foods, leaves, papers, clothing, leather, hair attachments, nylons, plastics, metals, and cans which often litter the dump environment. The economic cost of a sack-load of waste was *N200 in Iwo and N495 in Ibadan, and the frequency of waste removal is 150% higher in Iwo than in Ibadan. The average distance to the dumpsite is 2 km, which discourages low-income earners who are mostly pedestrians. Ibadan residents are culturally disposed to dirty streets and drainages/gutters with solid wastes; unfortunately, the situation in Iwo is not different. Stakeholder perceptions of factors impacting waste disposal in Iwo gave greater weight to (1) income and spending power, (2) culture, (3) religion, (4) governmental intervention, and (5) health factors in that order. In Ibadan, (1) income and spending power, (2) health factors, (3) occupational hazards, and (4) religion were rated in that sequence. It is conjectured that these issues demand strong attention in efforts to build functional capacities for solid waste disposal.